After He Jianku: China's biotechnology regulation reforms. (June 2021) - Song, Lingqiao; Joly, Yann
The unveiling of the world's first gene-edited twins by biophysics researcher He Jiankui generated much discussion about Chinese legal and ethical frameworks for biotechnology. In response, the highest Chinese legislative body, the National People's Congress, and the two responsible departments for biotechnology, the Ministry of Science and Technology and the National Health Committee, have undertaken a seemingly far-reaching regulatory reform. The most salient step of this reform is to regulate genetic research and human embryo research in the Chinese Civil Code. This article overviews recent policy developments in China and their respective importance for promoting a governance framework for biomedical research that meets the expectations of the international community. However, this regulatory reform could also set stricter administrative procedures in place for Chinese institutions and their foreign partners, which may impede scientific progress. The concrete impact of this reform on the practice of Chinese scientists will need to be closely scrutinised by Chinese authorities and the international community.